Combating Forced Labour : a Handbook for Employers and Business. Special Action Programme to Combat Forced Labour. - Office, International Labour (Geneva : International Labour Office, 2008)
This handbook provides guidance material and tools for employers and business to strengthen their capacity to address the risk of forced labour and human trafficking in their own operations and in global supply chains.
Combating Forced Labour 1: Introduction and Overview; Combating Forced Labour 2: Employers' Frequently Asked Questions; Combating Forced Labour 3: Guiding Principles to Combat Forced Labour; Combating Forced Labour 4: A Checklist & Guidance for Assessing Compliance; Combating Forced Labour 5: A Guide for Taking Action; Combating Forced Labour 6: Tips for Taking Action; Combating Forced Labour 7: Good Practice for Case Studies.
Print version record.
eBooks on EBSCOhost
Keywords: Employee rights; Forced labor; Labor laws and legislation, International; Business; Travail forcé.; Affaires; Personnel -- Droits; businesses (business enterprises); business (commercial function); BUSINESS & ECONOMICS -- Human Resources & Personnel Management; Business; Employee rights; Forced labor; Labor laws and legislation, International